On a Particular Construction of Skew‐Selfadjoint Operator Matrices. Issue 1 (21st October 2015) - Picard, Rainer; Seidler, Stefan; Trostorff, Sascha; Waurick, Marcus
Abstract We consider a particular construction for skew‐selfadjoint operator matrices, which are of central importance in initial boundary value problems of mathematical physics. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)